(untitled) (GIST – Education and Learning Research Journal, 2020)
This paper describes the results of the first cycle of a co-joint research study in methodological innovation in the initial education of pre-service language teachers. The experience consisted of the implementation of several learning strategies mediated by different ICT tools. These strategies were used by three teachers, in three different academic spaces of a B.A. in Spanish and Foreign Languages during the second semester of 2018. The purpose of this implementation was to examine the value of ICT-mediated learning strategies and gaining insights into how to integrate ICTs with a process of pedagogical and methodological innovation. The results of the data analysis, which were collected through a qualitative-quantitative survey, indicate that the integration of strategies mediated by ICTs seems to be essential for methodological and pedagogical innovation because they promote the development of collaborative and cooperative learning, foster autonomy and self-directed learning. Besides, these strategies also provide a range of possibilities for bolstering the development of the capacity of agency pre-service teachers.